Molecular investigations of the effect of thermal manipulation during embryogenesis on muscle heat shock protein 70 and thermotolerance in broiler chickens - Ali,Abdelhay Mohamed (2022)
ABSTRACT The objective of this study was to elucidate the optimum protocol timing of thermal manipulation (TM) during embryogenesis, which underline genetic improvement of muscle thermotolerance acquisition. For the present study, 1,440 fertile eggs were divided randomly and equally into control (37.8 °C with 56% relative humidity) and four thermally manipulated groups (TM1, TM2, TM3, and TM4) subjected to 39 °C for 18 h with 65% relative humidity daily during different embryonic periods. Then, at day 35 post-hatch, all groups were subjected to thermal challenge at 43 °C for 6 h to identify the level of thermotolerance acquisition differences between them. Hsp70 mRNA expression was evaluated by using a relative quantitatively RT-qPCR. Single nucleotide polymorphisms sequence of the Hsp70 gene was evaluated by Sanger's sequencing method. Pectoral and thigh muscles samples were subjected to immunohistochemistry to detect Hsp70. Among TM conditions that were investigated, TM1 (39 °C for 18 h during embryonic days (ED) 7–11) induced a significant improvement in thermotolerance parameters (body temperature and T3 levels) during thermal challenge combined with an increase in the levels of Hsp70 mRNA and its protein with a high stability of nucleotide sequences in both pectoral and thigh muscles. The partial DNA sequence of Hsp70 gene in TM1 was reported, and nucleotide sequences were deposited in NCBI GenBank database with the accession numbers (MK852579) and (MK852580). Thigh muscle thermotolerance acquisition was higher than pectoral muscle during thermal challenge at 43 °C for 6 h. Thus, TM during ED7–11 may improve thermotolerance acquisition without adversely affecting performance.